Evidence of complete gastric mill ossicle loss at ecdysis in the European green crab Carcinus maenas (Linnaeus, 1758) (Decapoda: Brachyura: Carcinidae). Issue 4 (12th June 2018) - Sheridan, Michael; O'Connor, Ian
Abstract: Several studies have identified the potential for determining age in decapod crustaceans using apparent growth increments present within the mesocardiac, zygocardiac, and pterocardiac ossicles of their gastric mill. For a number of species, however, doubts have been raised in relation to this method, with studies indicating that these ossicles are lost in the exuviae at ecdysis, partially resorbed during the premoult period, or lost internally and subsequently broken down and digested after ecdysis. We examined which ossicles of the gastric mill are lost and replaced at ecdysis in the European green crab Carcinus maenas (Linnaeus, 1758 ), as well as the possibility that some ossicles are retained throughout the moult cycle. Examination of the foregut of individuals sacrificed < 1 h after ecdysis revealed that all gastric mill and foregut ossicles are lost at ecdysis. New ossicles are calcified to form the gastric mill and support the foregut after ecdysis. The gastric mill ossicles not lost in the foregut exuvia were instead lost internally. A partially resorbed mesocardiac ossicle was present in the foregut exuvia, with the zygocardiac and partially resorbed pterocardiac ossicles lost internally and subsequently digested. This is the first time gastric mill ossicles of a brachyuran have been identified as being lost internally at ecdysis. A similar phenomenon was previously described as occurring in the lobster Nephrops norvegicus (Linnaeus, 1758 ) and the crayfish Austropotamobius pallipes (Lereboullet, 1858 ). The study raises further questions and doubts regarding the utility of gastric mill ossicles for determining age in decapod crustaceans.